CD4 T cells mediate brain inflammation and neurodegeneration in a mouse model of Parkinson's disease - Williams, Gregory P; Schonhoff, Aubrey M; Jurkuvenaite, Asta; Gallups, Nicole J; Standaert, David G; Harms, Ashley S (Brain (London, England : 1878), 2021)
α-Synuclein, a key pathological component of Parkinson's disease, has been implicated in the activation of the innate and adaptive immune system. This immune activation includes microgliosis, increased inflammatory cytokines, and the infiltration of T cells into the CNS. More recently, peripherally circulating CD4 and CD8 T cells derived from individuals with Parkinson's disease have been shown to produce Th1/Th2 cytokines in response to α-synuclein, suggesting there may be a chronic memory T cell response present in Parkinson's disease. To understand the potential effects of these α-syn associated T cell responses we used an α-synuclein overexpression mouse model, T cell-deficient mice, and a combination of immunohistochemistry and flow cytometry. In this study, we found that α-synuclein overexpression in the midbrain of mice leads to the upregulation of the major histocompatibility complex II (MHCII) protein on CNS myeloid cells as well as the infiltration of IFNγ producing CD4 and CD8 T cells into the CNS. Interestingly, genetic deletion of TCRβ or CD4, as well as the use of the immunosuppressive drug fingolimod, were able to reduce the CNS myeloid MHCII response to α-synuclein. Furthermore, we observed that CD4-deficient mice were protected from the dopaminergic cell loss observed due to α-syn overexpression. These results suggest that T cell responses associated with α-synuclein pathology may be damaging to key areas of the CNS in Parkinson's disease and that targeting these T cell responses could be an avenue for disease modifying treatments.α-Synuclein, a key pathological component of Parkinson's disease, has been implicated in the activation of the innate and adaptive immune system. This immune activation includes microgliosis, increased inflammatory cytokines, and the infiltration of T cells into the CNS. More recently, peripherally circulating CD4 and CD8 T cells derived from individuals with Parkinson's disease have been shown to produce Th1/Th2 cytokines in response to α-synuclein, suggesting there may be a chronic memory T cell response present in Parkinson's disease. To understand the potential effects of these α-syn associated T cell responses we used an α-synuclein overexpression mouse model, T cell-deficient mice, and a combination of immunohistochemistry and flow cytometry. In this study, we found that α-synuclein overexpression in the midbrain of mice leads to the upregulation of the major histocompatibility complex II (MHCII) protein on CNS myeloid cells as well as the infiltration of IFNγ producing CD4 and CD8 T cells into the CNS. Interestingly, genetic deletion of TCRβ or CD4, as well as the use of the immunosuppressive drug fingolimod, were able to reduce the CNS myeloid MHCII response to α-synuclein. Furthermore, we observed that CD4-deficient mice were protected from the dopaminergic cell loss observed due to α-syn overexpression. These results suggest that T cell responses associated with α-synuclein pathology may be damaging to key areas of the CNS in Parkinson's disease and that targeting these T cell responses could be an avenue for disease modifying treatments.